2023
DOI: 10.1021/acs.energyfuels.3c00196
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Asphaltene Dispersion Activity of Tetrabutylammonium Carboxylate Ionic Liquids

Abstract: Asphaltene destabilization is still known as one of the main problems of the petroleum industry and imposes many costs on this industry during crude oil production, transportation, and refining. The most important solution to control this problem is using chemical compounds to disperse asphaltene aggregates. Ionic liquids, as an emerging industrial solvent and catalyst, have been used for this purpose in the last two decades. In this work, three ionic liquids having a tetrabutylammonium cation and oleate, stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Ionic Liquid Additives. Three different re-synthesized ILs of TBAST, TBAOL, and TBACiN, which have been previously utilized as asphaltene dispersants by Baghersaei et al, 43 were employed to investigate their applicability for preventing or minimizing the asphaltene precipitation in the presence of injected water. To obtain detailed information on synthetic pathways of ILs, refer to the article of Baghersaei et al 43 The synthesized ILs and their structures are illustrated in Table 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic Liquid Additives. Three different re-synthesized ILs of TBAST, TBAOL, and TBACiN, which have been previously utilized as asphaltene dispersants by Baghersaei et al, 43 were employed to investigate their applicability for preventing or minimizing the asphaltene precipitation in the presence of injected water. To obtain detailed information on synthetic pathways of ILs, refer to the article of Baghersaei et al 43 The synthesized ILs and their structures are illustrated in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Ionic Liquid Characterization. After ILs' re-synthetization based on the study of Baghersaei et al, 43 hydrogen nuclear magnetic resonance ( 1 H-NMR) spectroscopy was performed to confirm their molecular structure, and its results are reported in SI. Since stearic acid, oleic acid, and cinnamic acid were employed to synthesize TBAST, TBAOL, and TBACiN, respectively, the absence of acidic H in the 1 H-NMR spectra confirmed that the synthesis reaction was performed completely.…”
Section: Effect Of Salinity and Saltmentioning
confidence: 99%
“…Among them, imidazolium ionic liquid with an alicyclic hydroxybenzene ring had the highest degree of hydrophobicity and demonstrated superior performance in dispersing asphaltenes and achieving significant viscosity reduction. Baghersaei et al [ 23 ] found that ionic liquids primarily stabilize asphaltenes through π–π and electrostatic interactions. The efficiency of asphaltene dispersion is directly related to the net negative anionic charge of the ionic liquid.…”
Section: Introductionmentioning
confidence: 99%